2020
DOI: 10.1111/cyt.12796
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognostic significance of incidentally detected cancer cells in uterine specimens of patients with pelvic high‐grade serous carcinoma

Abstract: Objective Cases of pelvic high‐grade serous carcinoma (HGSC) with incidentally detected cancer cells (ICCs) in endometrial and/or cervicovaginal cytology have been reported. This study aimed to clarify the incidence and characteristics of pelvic HGSC with ICCs and to determine whether ICCs have a negative prognostic impact. Methods Patients with ovarian/tubal/peritoneal HGSC who underwent pre‐treatment uterine (endometrial/cervicovaginal) cytology or biopsy between January 2007 and May 2017 were included. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Our literature review indicated that the positive rates of malignant cells in ascites cytology of ovarian cancer, fallopian tube cancer, and primary peritoneal cancer patients ranged from 18.1% to 85%, and 6.1% to 25% in cervicovaginal cytology [ Table 2 ]. [ 26 27 28 29 30 31 32 40 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our literature review indicated that the positive rates of malignant cells in ascites cytology of ovarian cancer, fallopian tube cancer, and primary peritoneal cancer patients ranged from 18.1% to 85%, and 6.1% to 25% in cervicovaginal cytology [ Table 2 ]. [ 26 27 28 29 30 31 32 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-seven case reports, case series, and two abstracts were excluded. Finally, seven retrospective studies[ 26 27 28 29 30 31 32 ] including 975 patients were identified [ Figure 1 ].…”
Section: R Esultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Jenkins et al recently reported that cervical serous carcinoma ( n = 6, HPV-negative) harbors mutations in TP53 (50%), KRAS (33%), PIK3CA (17%), and PTEN (17%) [ 44 ]. The possibility of drop metastasis in endometrial serous and adnexal HGSC should always be considered since tumor cells are detected in ~40% of uterine specimens in advanced HGSC [ 122 ]. Therefore, a diagnosis of cervical serous carcinoma should only be made after thorough and extensive sampling of the endometrium and fallopian tubes using the sectioning of the fimbriated end of the fallopian tube (SEE-FIM) technique.…”
Section: Pathology and Genetics Of Hpv-independent Cervical Cancermentioning
confidence: 99%